Continuing the evolution: Sustainable hrm and sustainable organizations? - Freitas, Wesley Ricardo S. [UNESP]; Jabbour, Charbel J.C. [UNESP]; Santos, Fernando Cesar A. [UNESP] (My University, 2012)
Purpose: In this article, we put sustainability as a new step in the evolutionary pathway of Human Resource Management (HRM). Design/methodology/approach: We did a literature review on the evolution of HRM and we reflected how HRM can contribute to organizational sustainability. Findings: We present a sustainable HRM as a new step in HRM evolution. We argue that Sustainable HRM is completely necessary to achieve sustainable organizations and a more sustainable society. Originality/value: Sustainability is becoming a key concept and a key element in the future of organizations, but little is known about the role of HRM in this process. © 2012 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Evolution; Human resource management; Sustainability